Faktor-Faktor yang Memengaruhi Niat Mahasiswa Akuntansi UNJ dalam Menggunakan Fintech Syariah - Daffa Nur Arkan; Nuramalia Hasanah; Hera Khairunnisa (PENG: Jurnal Ekonomi dan Manajemen, 2025)
This study aims to analyze the factors affecting the intention of UNJ Accounting students to use sharia fintech. The method used is quantitative with a survey instruments of 160 UNJ Accounting students who have taken Sharia Accounting courses. Sampling for research using non probability sampling technique with saturated sampling technique, where the population is sampled. The data analysis technique used Structural Equation Modeling Partial Least Square (SEM-PLS). The research findings prove that perceived ease of use, perceived usefulness, subjective norms, sharia compliance, and sharia financial literacy affect the intention to use sharia fintech. This provides theoretical implications that the integration of technological, social, and religious factors can explain the intention to use sharia fintech, as well as practical implications for service providers to present applications that are easy to use, educational, and in accordance with sharia principles to increase the intention of the younger generation.